The Influence of Chlorhexidine Diacetate Salt Incorporation Into Soft Denture Lining Material on Its Antifungal And Some Mechanical Properties - Altaf Qussay Abraham; Nabeel Abdul-Fattah (College of Dentistry/ University of Baghdad, 2017)
Background: One of the most common problem associated with the used of soft denture lining material is microorganisms and fungal growth especially Candida albicans, which can result in chronic mucosal inflammation. The aim of this study was to evaluate the influence of chlorhexidine diacetate (CDA) salt Incorporation into soft denture lining material on antifungal activity; against Candida albicans, and the amount of chlorhexidine di-acetate salt leached out of soft liner/CDA composite. Furthermore, evaluate shear bond strength and hardness after CDA addition to soft liner Materials and methods: chlorhexidine diacetate salt was added to soft denture lining material at four different concentrations (0.05%, 0.1% and 0.2% by weight). Four hundred and fifty specimens were made and divided into four groups according to the test to be performed. Disk diffusion test was used to evaluate the antifungal activity of the soft liner/CDA composite after four different periods of incubation in artificial saliva. UV spectroscopy was used to evaluate the amount of accumulative and periodic CDA released in artificial saliva after 2 days, 2 weeks and 4 weeks incubation in artificial saliva. The shear bond strength and shore A hardness was measured after 2 and 4 weeks incubation in artificial saliva and the results were statistically analyzed. Results: All experimental groups showed a highly significant increase in diameter of inhibition zone around the test specimen in compare with control group. The release of Chlorhexidine showed to be dose dependent. The shore A hardness a highly significant increase with the addition of CDA and as for shear bonding strength, the addition of CDA at 0.5% and 1.5% percentage resulted in a highly significant decrease in bond strength, while 2.5% and 3.5% percentage showed non-significant differences in compare with control. Conclusion: soft denture lining material with antifungal properties was the result of CDA salt incorporation which indicate that chlorhexidine was released in affected concentration from soft liner/CDA composite. This incorporation resulted in Hardness increase and did not affect the shear bond strength for 2.5% and 3.5% percentage. Keywords: Soft denture liners, antifungal activity, chlorhexidine diacetate salt.